Pedagogical Leadership for Strengthening Local Wisdom-Based Character Learning: A Case Study of Ketek Ogleng Cultural Education in an Indonesian Elementary School - Setyani, Netty Dwi; Raharja, Setya (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Local wisdom-based character education has gained increasing attention as an approach to fostering meaningful learning experiences while preserving cultural heritage in elementary education. However, limited research has examined how pedagogical leadership supports the integration of local cultural practices into character learning within school settings. This study explores the role of pedagogical leadership in strengthening local wisdom-based character learning through the implementation of Ketek Ogleng cultural education at SDN 2 Sempu, Indonesia. Employing a qualitative single-case study design, data were collected through in-depth interviews with the principal, teachers, school committee representatives, and local cultural practitioners, complemented by participant observations and document analysis. The findings indicate that pedagogical leadership was reflected in the school's vision, curriculum integration, resource management, collaboration with local artists, and continuous supervision of learning activities. Ketek Ogleng was implemented as an experiential learning medium that enabled students to internalize values of discipline, responsibility, cooperation, cultural appreciation, and respect for local traditions through authentic participation in cultural performances. The findings further demonstrate that the principal's leadership extended beyond administrative management by creating a culturally responsive learning environment that connected classroom learning with community cultural resources. This pedagogical approach strengthened students' character development while promoting the preservation of local cultural heritage. The study concludes that pedagogical leadership plays a pivotal role in sustaining local wisdom-based learning ecosystems and recommends a structured pedagogical framework for integrating indigenous cultural resources into elementary education to support character development and culturally responsive learning.